What is the solution to the equation 6y –2(y + 1) = 3(y – 2) + 6? y = –10 y = –2 y = 2 y = 6

Question

What is the solution to the equation 6y –2(y + 1) = 3(y – 2) + 6?
y = –10
y = –2
y = 2
y = 6

in progress 0
Kiệt Gia 1 month 2021-08-02T08:22:21+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-08-02T08:23:56+00:00

    6y –2(y + 1) = 3(y – 2) + 6?

    The answer is y = 2 (the third option.)

    0
    2021-08-02T08:24:14+00:00

    Answer:

    y = 2

    Step-by-step explanation:

    6y-2(y+1)=3(y-2)+6\\\\6y-2y-2=3y-6+6\\\\4y-2=3y\\\\4y-2=3y\\\\4y-2+2=3y+2\\\\4y=3y+2\\\\4y-3y=3y-3y+2\\\\\boxed{y=2}

    Hope this helps.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )